Divergence With Gene Flow and Contrasting Population Size Blur the Species Boundary in Cycas Sect. Asiorientales, as Inferred From Morphology and RAD-Seq Data - Chang, Jui-Tse; Chao, Chien-Ti; Nakamura, Koh; Liu, Hsiao-Lei; Luo, Min-Xin; Liao, Pei-Chun (Frontiers in Plant Science, 2022)
The divergence process of incipient species is fascinating but elusive by incomplete lineage sorting or gene flow. Species delimitation is also challenging among those morphologically similar allopatric species, especially when lacking comprehensive data. Cycas sect. Asiorientales, comprised of C. taitungensis and C. revoluta in the Ryukyu Archipelago and Taiwan, diverged recently with continuous gene flow, resulting in a reciprocal paraphyletic relationship. Their previous evolutionary inferences are questioned from few genetic markers, incomplete sampling, and incomprehensive morphological comparison by a long-term taxonomic misconception. By whole range sampling, this study tests the geographic mode of speciation in the two species of Asiorientales by approximate Bayesian computation (ABC) using genome-wide single nucleotide polymorphisms (SNPs). The individual tree was reconstructed to delimit the species and track the gene-flow trajectory. With the comparison of diagnostic morphological traits and genetic data, the allopatric speciation was rejected. Alternatively, continuous but spatially heterogeneous gene flow driven by transoceanic vegetative dispersal and pollen flow with contrasting population sizes blurred their species boundary. On the basis of morphological, genetic, and evolutionary evidence, we synonymized these two Cycas species. This study highlights not only the importance of the Kuroshio Current to species evolution but also the disadvantage of using species with geographically structured genealogies as conservation units.